2011
DOI: 10.1186/1471-2148-11-41
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization and splicing evolution of the doublesex gene, a Drosophila regulator of sexual differentiation, in the dengue and yellow fever mosquito Aedes aegypti

Abstract: BackgroundIn the model system Drosophila melanogaster, doublesex (dsx) is the double-switch gene at the bottom of the somatic sex determination cascade that determines the differentiation of sexually dimorphic traits. Homologues of dsx are functionally conserved in various dipteran species, including the malaria vector Anopheles gambiae. They show a striking conservation of sex-specific regulation, based on alternative splicing, and of the encoded sex-specific proteins, which are transcriptional regulators of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
112
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 60 publications
(79 reference statements)
1
112
1
1
Order By: Relevance
“…It is thus likely that tra is a part of an ancestral module, which relays the instructive signals to downstream effectors. The gene doublesex (dsx) has been identified as a prime target of tra in all insect systems studied so far [Burtis and Baker, 1989;Shearman and Frommer, 1998;Kuhn et al, 2000;Ohbayashi et al, 2001;Suzuki et al, 2001;Hediger et al, 2004;Scali et al, 2005;Ruiz et al, 2007a;Oliveira et al, 2009;Concha et al, 2010;Shukla and Nagaraju, 2010;Salvemini et al, 2011;Shukla and Palli, 2012a]. In addition, there is growing evidence which suggests that the pathway below tra bifurcates employing a different target, the fruitless gene (fru) , for sex-specific differentiation of CNS-related aspects such as male courtship behavior [Bertossa et al, 2009;Salvemini et al, 2010;Clynen et al, 2011;Meier et al, 2013].…”
Section: Insects Employ a Conserved Module In Transducing Sex-determimentioning
confidence: 99%
“…It is thus likely that tra is a part of an ancestral module, which relays the instructive signals to downstream effectors. The gene doublesex (dsx) has been identified as a prime target of tra in all insect systems studied so far [Burtis and Baker, 1989;Shearman and Frommer, 1998;Kuhn et al, 2000;Ohbayashi et al, 2001;Suzuki et al, 2001;Hediger et al, 2004;Scali et al, 2005;Ruiz et al, 2007a;Oliveira et al, 2009;Concha et al, 2010;Shukla and Nagaraju, 2010;Salvemini et al, 2011;Shukla and Palli, 2012a]. In addition, there is growing evidence which suggests that the pathway below tra bifurcates employing a different target, the fruitless gene (fru) , for sex-specific differentiation of CNS-related aspects such as male courtship behavior [Bertossa et al, 2009;Salvemini et al, 2010;Clynen et al, 2011;Meier et al, 2013].…”
Section: Insects Employ a Conserved Module In Transducing Sex-determimentioning
confidence: 99%
“…Strictly speaking, it is not appropriate to talk in terms of default dsx pre-mRNA splicing in Sciara because both male and female dsx mRNAs are simultaneously produced in the two sexes. Sciara could parallel the situation hypothesized in Aedes (Salvemini et al 2011); that is, putative SR-M and SR-F splicing factors, which would be functional in males and females, respectively, are present in both sexes, but in Sciara these factors would be simultaneously functional in both sexes. 3.…”
Section: Comparison Of the Dsx Proteins Of Sciara With Those Of Othermentioning
confidence: 96%
“…No putative NvdsxRE sites for TRA-TRA2 binding were found. These sequences, which have been found in the hymenopteran Nasonia dsx (Verhulst et al 2010), have been also observed in the dsx gene of Aedes (Salvemini et al 2011) and Tribolium (Shukla and Palli 2012). Finally, no BmPSI-exonic splicing suppressor (BmPSI-ESS) sequences were detected in Scdsx pre-mRNA.…”
mentioning
confidence: 89%
See 2 more Smart Citations